2019
DOI: 10.5539/gjhs.v11n14p119
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Learning Burnout among Special Education Students

Abstract: This study examined gender differences in learning burnout among special education students. A research question and a null hypothesis were formulated to guide the research. A descriptive survey was employed. The study sample consisted of 700 special education students. Academic Burnout Questionnaire (ABQ) was employed for data collection. The research data were analyzed using mean, standard deviation and t-test. The finding of the study revealed that there is no significant difference between the mean ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…Our findings showed that there is no significant difference in mean academic burnout among the students. This finding is in line with a study which explored gender differences in burnout of students in Nigeria (Arumede et al, 2019). Furthermore, a previous study showed among 36 postgraduate students, a no significant difference in pretest mean burnout scores (Ezeudu, et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings showed that there is no significant difference in mean academic burnout among the students. This finding is in line with a study which explored gender differences in burnout of students in Nigeria (Arumede et al, 2019). Furthermore, a previous study showed among 36 postgraduate students, a no significant difference in pretest mean burnout scores (Ezeudu, et al, 2019).…”
Section: Discussionsupporting
confidence: 91%